THE IMPACT OF THE WTO TRADE REGULATION ON THE RUSSIA-EUROPEAN UNION ENERGY DIALOGUE - Yu. M. Kukushkina (Финансы: теория и практика, 2017)
The article analyzes the influence of the WTO regulation function on energy markets in general. The WTO system does not include any specific agreement on energy trading for historical reasons. However, with new WTO members, who export hydrocarbons, including Russia, the regulation of energy sales is becoming more important. The analysis of theoretical papers and the WTO legislation identifies WTO rules that indirectly influence the global energy market. Hence, the analysis in the article is focused on consequences of Russia’s WTO accession in different aspects of the energy dialogue with the EU. As a result, the author demonstrates problematic issues in the Russia-EU energy cooperation and the way the WTO solves or complicates them for Russia. Moreover, there is a comprehensive analysis of current and potential disputes between Russia and the EU, and prospects of their settlement by means of a special WTO Dispute Settlement Body.